Avidity of polyreactive immunoglobulins - S. A. Bobrovnik (The Ukrainian Biochemical Journal, 2014)
An analysis of the mechanism of interaction between polyreactive immunoglobulins (PRIG) and antigen was conducted and it was shown that most of the traditional methods of antibody affinity evaluation are not applicable for PRIG affinity. The comparative assessment of the mouse and human PRIG avidity against ovalbumin and horse myoglobin and the avidity of specific monoclonal antibodies against ovalbumin have shown that the avidity of PRIG not only is much less than the avidity of monoclonal antibodies but even exceeds it.